Malaysian youth political participation - Fadzil, Mohd. Fauzi; Ismail, Ismi Arif; Krauss, Steven Eric (Human Resource Management Academic Research Society, 2022)
The previous literature had show that low political participation of Malaysian youth, the effect of this situation will be discuss further in this article regarding youth development. This article use narrative literature review method to get the suitable article to be reviewed. Focus of this article are upon critical analysis of the literature published in books, electronic or paper-based journal articles, report and seminar paper. This article will help to developed the studies on the challenge and benefit of Malaysian youth participation in politics in several field. It can be seen today the negative narrative of adult towards youth have institutionalizes into programs and policy which make building the youth potential becomed harder. Youth political participation in Malaysia from literature show that they are inclined to get information from internet, involved with platform such as youth parliament and active as general election voters. There are four challenge that faced by effort for youth political participation in Malaysia which is the idea of youth participation is accomplished by placing one youth on a board or committee, the idea of youth participation means that adults surrender their roles as guides and educators, the idea of adults are ready for youth participation and the last one is the idea of adults are ready for youth participation. The answer for youth political participation is the development of physical space where youth can participate with political organization and enhance thier potential. The way forward is for all political and youth organization to start providing a physical space for thier youth member to organized and used it as thier creativity allow them. The issue of youth political participation in Malaysia today show that the adult are still given a room for youth participation, but the room for the participation are too small and limited.